Increasing Workplace Diversity: Evidence from a Recruiting Experiment at a Fortune 500 Company - Jeffrey A. Flory; Andreas Leibbrandt; Christina Rott; Olga Stoddard (Center for Economic Studies and ifo Institute (CESifo), 2018)
The persistent lack of workplace diversity in management and leadership may lead to organizational vulnerabilities. White males occupy most high-profile positions in the largest U.S. corporations whereas African Americans, Hispanics, and women are clearly underrepresented in leadership roles. While many firms and other organizations have set ambitious goals to increase demographic diversity, there is a dearth of empirical evidence on effective ways to reach them. We use a natural field experiment to test several hypotheses on effective means to attract minority candidates for top professional careers. By randomly varying the content in recruiting materials of a major financial services corporation with over 10,000 employees, we test different types of signals regarding the extent and manner in which the employer values diversity among its workers. We find that signaling explicit interest in employee diversity can reverse the ethnicity gap in rates of interest and applications, and that it has a strong positive effect on interest in openings among racial minority candidates, the likelihood that they apply, and the probability that they are selected. These results uncover an effective method for disrupting monocultures in management through a minor intervention that influences sorting among job-seekers into high-profile careers.
Keywords: J15; J16; C93; D22; 330; diversity; experiment; field experiment; gender; race